The oriented development of antituberculotics: salicylanilides - Waisser, Karel; Matyk, Josef; Divišová, Hana; Husáková, Petra; Kuneš, Jiří; Klimešová, Věra; Kaustová, Jarmila; Möllmann, Ute; Dashe, Hans-Martin; Miko, Milan (Archiv der Pharmazie, 2006)
On the basis of our previous results 22 salicylanilides were synthesized. The compounds were tested for in vitro antimycobacterial activity against Mycobacterium tuberculosis, Mycobacterium kansasii, and Mycobacterium avium. The Free-Wilson method was used to evaluate structure-antimycobacterial activity relationships. 4-Chloro-N-(4-propylphenyl)salicylamide and 5-chloro-N-(4-propylphenyl)salicylamide were selected for preclinical studies.
Keywords: Antitubercular Agents; Mycobacterium kansasii; Structure-Activity Relationship; Salicylanilides; Financing, Organized; Mycobacterium avium; salicylanilidy; financování organizované; Microbial Sensitivity Tests; mikrobiální testy citlivosti; antituberkulotika; Mycobacterium tuberculosis; vztahy mezi strukturou a aktivitou